2000
DOI: 10.15760/etd.27
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Encoding Of Vocalizations In The Auditory Midbrain

Abstract: An important question in sensory neuroscience is what coding strategies and mechanisms are used by the brain to detect and discriminate among behaviorally relevant stimuli. To address the noisy response properties of individual neurons, sensory systems often utilize broadly tuned neurons with overlapping receptive fields at the system's periphery, resulting in homogeneous responses among neighboring populations of neurons. It has been hypothesized that progressive response heterogeneity in ascending sensory pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 85 publications
1
17
0
Order By: Relevance
“…Therefore, the responsiveness of a neuron to all the signal types ( Fig. 2) relative to the responsiveness to the natural wriggling call was expressed by the selectivity index as used by others (Wang & Kadia, 2001;Holmstrom et al, 2010) d = (n 0 À n)/ (n 0 + n) with n 0 equal to the number of spikes to 19 repetitions of the natural wriggling call and n to the number of spikes to 19 repetitions of a given signal type. d was calculated separately for on-responses and, if applying, offresponses of a given unit.…”
Section: Analysis Of Responses To the Natural Wriggling Call And The mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the responsiveness of a neuron to all the signal types ( Fig. 2) relative to the responsiveness to the natural wriggling call was expressed by the selectivity index as used by others (Wang & Kadia, 2001;Holmstrom et al, 2010) d = (n 0 À n)/ (n 0 + n) with n 0 equal to the number of spikes to 19 repetitions of the natural wriggling call and n to the number of spikes to 19 repetitions of a given signal type. d was calculated separately for on-responses and, if applying, offresponses of a given unit.…”
Section: Analysis Of Responses To the Natural Wriggling Call And The mentioning
confidence: 99%
“…Off-responses in addition to on-responses to single tones at the CF of a neuron have been observed in mouse IC neurons before at rates of 3-12% depending on the SPL of the stimulus (Ehret & Moffat, 1985;Egorova, 2008a, b;Kasai et al, 2012). Off-responses in the IC to mouse ultrasonic vocalizations have been recorded but not separated from and quantified in addition to on-responses (Holmstrom et al, 2010). Similarly, on-and off-responses to vocalizations have been recorded from the guinea pig IC but not analyzed further ( Suta et al, 2003).…”
Section: Off-response Occurrencementioning
confidence: 99%
“…It is likely that the involvement of multiple neural mechanisms enables the IC to encode UHFs and process complex sounds that contain them (e.g., vocalizations) more accurately (Holmstrom et al, 2010). It is plausible that the combination (i.e., summation) and distortion (i.e., difference) of two UHFs contain complementary signals, with which the IC can fully decode and extract information conveyed in both frequency channels.…”
Section: Uhf Encoding In the Icmentioning
confidence: 99%
“…For example, in the primary auditory nucleus in the midbrain, called the inferior colliculus (IC), which is a compulsory relay for all ascending auditory projections (Malmierca, 2003) and a region that efficiently encodes vocalizations (Holmstrom et al, 2010), the tonotopic organization is a basic feature in its central nucleus (CNIC), where the CFs of neurons run from low to high along the dorsolateralventromedial dimension (Cheung et al, 2012a(Cheung et al, , 2012bDe Martino et al, 2013;Malmierca et al, 2008;Ress and Chandrasekaran, 2013;Schreiner and Langner, 1997;Yu et al, 2005). In the cortical regions of the IC, the frequency organization is usually non-tonotopic, with neurons showing complex frequency tuning properties, such as broadband or multipeak receptive fields (Duque et al, 2012;Hernandez et al, 2005;Malmierca et al, 2011;Stebbings et al, 2014).…”
mentioning
confidence: 99%
“…In particular, it has been shown that the heterogeneity in firing patterns of MT neurons in the visual cortex of primates leads to an increase in information coding (Osborne et al 2008). Another study showed that heterogeneity of the population response of neurons in the inferior colliculus of mammals permits the discrimination of different vocalizations (Holmstrom et al 2010). Sensory coding is often referred to as sparse in higher brain areas because only a few neurons respond to a given feature of the sensory signal so that these features are not redundantly encoded in a large population of neurons (Olshausen and Field 2004).…”
Section: Heterogeneity and Population Coding Efficiencymentioning
confidence: 99%